LIBER/OCLC Fund for Central and East European Libraries - LIBER Quarterly (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The Ligue des Bibliotheques Europeennes de Recherche (LIBER) is delighted to announce the LIBER/OCLC Fund for Central and East European Libraries, which is generously supported by OCLC. The Fund will offer membership of LIBER to individual libraries in Central and Eastern Europe for a period of years in order to assist them to support their membership of LIBER from their own resources at the end of the period of support from the Fund.